142 Discordance between neurologists and people with MS on the presence and burden of cognitive impairment - Penner, Iris Katharina; Heras, Virginia de las; Jones, Eddie; Castro, Patricia Dominguez; Bezlyak, Vladimir; Piani-Meier, Daniela; Lines, Carol (Journal of neurology, neurosurgery and psychiatry, 2022)
IntroductionApproximately 34%-65% of people with multiple sclerosis (pwMS) develop cognitive impair- ment (CI). CI often encompasses information processing speed, memory problems, difficulty concentrat- ing, and problems using executive functions effectively. This study explores the perception of the presence of CI from the perspectives of pwMS and neurologists.MethodsUS, UK and EU retrospective data analysis from the 2011-2019 Adelphi Multiple Sclerosis Disease- Specific Programme (MS-DSP). The MS-DSP is a database where neurologists provide data on the next 10 pwMS to have a consultation, patient record form (PRF), integrated with pwMS self-reported data, patient self-completion form (PSC). Neurologists and pwMS were asked about the presence of problems concentrating.Results25,374 pwMS had a PRF. 11,220 pwMS had a PRF and PSC, of these 4294 answered the cognition section, with 62% (n=2,643) reporting CI (mild 36.8%, moderate 18.6, or extreme 6.1% problems concen- trating) in the past two weeks. For the same pwMS, neurologists reported 27% (n=1,158) currently having CI (mild 19.9%, moderate 6.8%, or severe 0.3% problems concentrating).ConclusionsA clear discordance is observed between neurologists and pwMS on their perception of the presence and severity of CI with neurologists clearly underestimating the existence. Funding: Novartis Pharma AG, Basel, Switzerland.